1978
DOI: 10.1136/bmj.2.6134.397
|View full text |Cite
|
Sign up to set email alerts
|

Ileal loop carcinoma after cystectomy for bladder exstrophy.

Abstract: temperature was infused at a rate of 2-5-3 1/h. The patient was then seated on a cushioned rubber ring on a commode in a secluded, warm, and wellventilated room. The infusion was continued until the effluent started to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…As reported, the first case of carcinogenesis in ureterosigmoidostomy was described in 1929 However, only after knowing the first case of neoplasia in a uretero-ileal diversion, studies were initiated on oncogenesis in urinary diversions, since the feces could not have been the causative factor 13 . It should be noted that the time of observation in our study was 30 weeks the equivalent of 7.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…As reported, the first case of carcinogenesis in ureterosigmoidostomy was described in 1929 However, only after knowing the first case of neoplasia in a uretero-ileal diversion, studies were initiated on oncogenesis in urinary diversions, since the feces could not have been the causative factor 13 . It should be noted that the time of observation in our study was 30 weeks the equivalent of 7.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of carcinoma in ileal conduits has been noted [15][16][17][18]. Most of these cases have been related to ileal conduits performed with cystectomy for cancer 115.…”
Section: Discussionmentioning
confidence: 99%
“…16]. Other cases have occurred without a known primary, though these are rare [17,18]. Hanke et al [19] recently evaluated ileal conduit biopsies with routine histological studies and scanning electron-microscopic techniques and found signs of chronic inflammation and a reduction in the number of microvilli per cell.…”
Section: Discussionmentioning
confidence: 99%
“…On these criteria, the risk of malignancy in isolated colonic conduits should be relatively insignificant, whereas the risk of cancer in ileal conduits should be intermediate between the risks with the two alternative forms of diversion. The first malignancy (adenocarcinoma) in an ileal loop was described by Shousha, Scott and Polak, (1978), 20 years after the diversion was performed for exstrophy. If our hypothesis is correct, and assuming a similar latency to that of malignancy at the ureterocolic anastomosis, this case may be the warning of many more to come.…”
Section: Discussionmentioning
confidence: 99%